2007
DOI: 10.1007/s00402-007-0457-x
|View full text |Cite
|
Sign up to set email alerts
|

Arthrodesis of the distal interphalangeal joint: description of a new technique and clinical follow-up at 2 years

Abstract: The technique is simple and reliable giving consistent clinical results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 12 publications
1
21
0
6
Order By: Relevance
“…Because each technique has its own advantages and problems, no single technique has gained universal popularity. Early techniques such as a single K-wire, crossed K-wires and intraosseous wiring provided stabilization of the joint but produced poor compression of the fusion surfaces [13][14][15]. The complication rate of these early techniques was high, with hardware protrusion or migration, loosening, nonunion, pin-track infections, dorsal skin necrosis, osteomyelitis, or stiffness of the adjacent joint [3].…”
Section: Discussionmentioning
confidence: 96%
“…Because each technique has its own advantages and problems, no single technique has gained universal popularity. Early techniques such as a single K-wire, crossed K-wires and intraosseous wiring provided stabilization of the joint but produced poor compression of the fusion surfaces [13][14][15]. The complication rate of these early techniques was high, with hardware protrusion or migration, loosening, nonunion, pin-track infections, dorsal skin necrosis, osteomyelitis, or stiffness of the adjacent joint [3].…”
Section: Discussionmentioning
confidence: 96%
“…2,11 Several studies have reported the results of compression screw techniques, ranging from 0% to 15% nonunion and from 14% to 44% overall complications (Table 1). 2,4,6,12,13 The oblique placement of an AO lag screw has been reported to result in nonunion in 4% of cases Figure 2 showing the screw correctly placed and good bone coaptation. at 8 weeks' mean follow-up.…”
Section: Discussionmentioning
confidence: 98%
“…1 Arthrodesis is commonly performed for symptomatic arthritis at the DIP joint. [1][2][3][4][5] A variety of arthrodesis techniques have been described. 1,2,[5][6][7][8] Whereas favorable results have been reported, rates of nonunion and implant-related complications remain considerable.…”
mentioning
confidence: 99%
“…4,5,8,9,15 High level evidence-based recommendations for splint therapy for osteoarthritis of the DIP joint have not been established, 11,12,16 -18 in contrast to studies of osteoarthritis of the carpometacarpal joint or wrist joint that have been more carefully described. 13,19 According to previous studies that examined hand splints for osteoarthritis of the carpometacarpal joint and wrist joint, the primary focus is the patient's motivation and compliance in using the splint.…”
Section: Discussionmentioning
confidence: 91%
“…For the latter, surgical interventions such as arthrodesis are often required. [1][2][3][4][5] For cases with early-stage symptoms and at earlier radiographic stage, nonsurgical treatments such as medication with nonsteroidal anti-inflammatory drugs 6,7 or immobilization with a splint 8,9 have been recommended. Although osteoarthritic changes are also partly related to the normal aging phenomenon and occasionally progress to joint destruction, acute flare-up symptoms may often resolve in the long run.…”
mentioning
confidence: 99%